Utilization of Hill Climbing Algorithm in Optimizing the Shortest Route to Tourist Destinations in Surabaya City - M. Rafi Ardiansyah; Rendra Ardika; Moh. Misbahul Musthofah; Anggraini Puspita Sari (Brilliant International Journal Of Management And Tourism, 2025)
Surabaya City holds significant tourism potential with various popular destinations such as Taman Bungkul, the Submarine Monument, and Kenjeran Beach. However, the large number of attractions and limited visiting time often make it difficult for tourists to plan efficient travel routes. To address this issue, this study aims to implement the Hill Climbing algorithm to optimize the shortest path among tourist destinations in Surabaya. The method uses a heuristic approach by iteratively swapping the positions of two locations in the travel route to find an optimal solution that minimizes total travel distance. The developed system features a GUI-based interface, graphical visualization using the networkx and matplotlib libraries, and direct integration with Google Maps to facilitate user navigation. Testing results indicate that the Hill Climbing algorithm can generate more efficient travel routes compared to randomly ordered routes. These findings contribute to the development of intelligent and practical travel planning systems..